Immunohistochemical Expression of P53 In Low-Grade and High-Grade Papillary Urothelial Carcinoma of the Bladder - Khurshid, Shaista (International Journal of Pathology, 2023)
Introduction: Bladder cancer is the fourth most common genitourinary malignancy with urothelial carcinomas comprising 90% of all primary bladder carcinomas. The protein TP53 is a nuclear phosphoprotein that acts as a tumor suppressor gene. Being a regulator of cell proliferation and pro-apoptotic gene, a mutation in p53 can nullify its normal functions and increased expression of the mutant protein is regarded as a predictor of poor prognosis of urothelial tumors. Objective: To compare and determine the immunohistochemical expression of p53 gene overexpression in low and high-grade Papillary urothelial carcinoma. Material and Methods: This cross-sectional study was done in the Histopathology section of the Department of Pathology, Pakistan Institute of Medical Sciences from March 2014 to April 2015. It included 65 cases of urothelial carcinomas. Immunohistochemical expression of p53 was performed according to standard protocols and correlated with age, sex, grade, and depth of invasion(stage). Results: Out of the total 65 cases, 22 (33.2%) low-grade and 43 (66.2%) high-grade urothelial carcinoma cases were included in the study. Positive expression of p53 was seen in 41 (95.3%) cases of high-grade, and 12 (54.5%) cases of low-grade tumors. Conclusion: The evaluation of p53 nuclear overexpression combined with histological grade and pathological stage may give more accurate information about the biological behavior of urothelial carcinoma of the urinary bladder